Highly durable antibacterial surface through in-situ grown copper nanoparticles for biomedical applications - Sahin, Furkan; Sahin, Gamze Demirel; Ceylan, Ahmet; Onses, Mustafa Serdar (IEEE, 2022)
Infectious diseases are serious threat to the human health and safety. Traditional methods to overcome this challenge are less effective due to emergence of resistant strains. Therefore, low cost, efficient novel antibacterial materials may be powerful alternative to combat bacteria. In this study, we present a single step, in-situ fabrication approach to antibacterial surfaces. Herein, copper nanoparticles were in-situ grown and the morphology of the paper surface was characterized with scanning electron microscopy (SEM). Energy-dispersive X-ray spectroscopy (EDX) was used to understand the composition of the surface and EDX mapping for location of the elements. It was seen that, Cu nanoparticles successfully grew on the surface and distributed homogeneously. Furthermore, feasibility of the approach for various application area was demonstrated in the glove, fabric, paper and PDMS surfaces. Moreover, mechanical stability of the surfaces was evaluated. As an advantage of in situ copper growth, the surfaces retained their antibacterial activity after mechanical abrasion and washing. Obtained results show that, developed antibacterial surface fabrication approach may provide a powerful, effective, low-cost and stable platform to combat bacteria.
Keywords: antibacterial; durable; copper nanoparticles; surface; Cell Biology; Engineering